Impact of Medicinal Cannabis as an Adjunct to Conventional Therapy in Diabetic Neuropathy - Mustafa Yassin; Dror Robinson (Medical Science: Trends and Innovations Vol. 3, 2025)
Background: Diabetes mellitus is increasing in prevalence in the Western world. Its estimated prevalence currently is about 30 percent of diabetic people making it the most common complication of diabetes. Diabetic neuropathy is unfortunately the most common complication associated with a common malady increasing in prevalence by 5% a year. None of the disease-modifying drugs that have been designed to target multiple metabolic pathways has proven effective. Thus, the treatment currently is mostly symptomatic. The current study assessed the ability of cannabis added to maximal conventional therapy to ameliorate diabetic neuropathy symptoms. Methods: At screening, patients were assessed for the possibility of being treated by receiving cannabis therapy (CT, smoking, 20 grams per month) provided that they have completed a period of at least 12 months of optimal conventional treatment including at least one narcotic agent and at least one of following analgesic treatments: tricyclic antidepressants (amitriptyline and nortriptyline), anticonvulsants (gabapentin and pregabalin), and Serotonin- Norepinephrine Reuptake Inhibitors (SNRIs) (duloxetine and venlafaxine). Patients suitable for CT were treated for at least 3 months more with alpha lipoic acid 600 mg, vitamin B complex, duloxetine 30 mg and tramadol 100 mg up to thrice a day. If after 3 months of treatment, the patients were still in pain (BPI pain severity higher than 7) cannabis therapy was begun. Patients were followed up every 6 months for up to one year. The following Patient Reported Outcome scores (PROs) were collected: VAS pain intensity, VAS pain severity, BPI pain severity, BPI pain interference and SF12. Results: In this study, 89 patients were screened. Out of 89, 15 improved after 3 months of maximal conventional therapy and thus did not meet the inclusion criteria of minimal pain severity. 74 patients began cannabis therapy and results are available after 6 months for 73 of them and 70 patients were followed up to 12 months. 4/74 patients stopped CT (1/74 due to ileus, 3/74 due to pain resolution). BPI pain severity decreased from 9.4±0.8 to 4.3±1.7 at six months, while pain interference decreased from 8.6±1.1 to 3.7±1.6. SF12v2 Physical Compounded Score (PCS) changed from 34±8 to 46±8 at 6M. Conclusions: The addition of CT leads to substantial pain reduction accompanied by a decrease in HbA1C while quality of life questionnaire scores improved. The mechanism leading to improved diabetic control is not known at this time and requires further study. Further clinical research is necessary in order to define whether long-term MCT will lead to improved nerve function, as the time frame of this study is too short to allow nerve regeneration.